Elaboración de un plan para mejorar la seguridad informática de la Municipalidad Distrital de San Juan Bautista - 2021 - Vílchez Guevara, Brigitte Betsabé (2023)
The present research addresses the relevance and importance of all public entities having an Information Security Plan based on the controls provided by ISO/IEC 27002:2013 standard, as information must be kept secure. Considering this issue in the District Municipality of San Juan Bautista, we pose the following question: What is the level of implemented information security in the District Municipality of San Juan Bautista? To achieve this, the research aimed to develop an Information Security Plan based on the ISO/IEC 27002:2013 standard, in order to assess and strengthen the security of information assets within the entity. A quantitative approach with a simple descriptive design was employed, evaluating a sample of 680 information assets used for collecting, processing, and storing data in the District Municipality of San Juan Bautista. Data was collected through checklists, surveys, interviews with the IT manager, and observation records. The results confirmed the research hypothesis, demonstrating that: "The level of risk associated with the information assets of the District Municipality of San Juan Bautista is low."